2020
DOI: 10.1002/jgc4.1324
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized trial of an educational intervention to increase genetic counseling and genetic testing among Latina breast cancer survivors

Abstract: Latinas are less likely to participate in genetic counseling (GC) and genetic testing (GT) than non‐Hispanic Whites. A multisite, randomized pilot study tested a culturally targeted educational intervention to increase uptake of GC/GT among Latina breast cancer (BC) survivors (N = 52). Participants were recruited in Tampa, FL and Ponce, PR and randomized to: (a) fact sheet about BC survivorship (control) or (b) a culturally targeted educational booklet about GC/GT (intervention). Participants in the interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(56 citation statements)
references
References 74 publications
1
55
0
Order By: Relevance
“…Considerations for interventions should be across different levels of the socioecological model (Stokols, 1992 ) to ensure that individual‐level solutions and system‐level solutions are examined. Examples of solutions include culturally targeted and sensitive educational materials (Conley et al., 2021 ; Henderson et al., 2021 ), interactive digital programs (Wang et al., 2021 ), and patient outreach and system navigation efforts (Mays et al., 2012 ).…”
Section: Future Research Considerations To Help Ensure Equitable Access and Benefitmentioning
confidence: 99%
“…Considerations for interventions should be across different levels of the socioecological model (Stokols, 1992 ) to ensure that individual‐level solutions and system‐level solutions are examined. Examples of solutions include culturally targeted and sensitive educational materials (Conley et al., 2021 ; Henderson et al., 2021 ), interactive digital programs (Wang et al., 2021 ), and patient outreach and system navigation efforts (Mays et al., 2012 ).…”
Section: Future Research Considerations To Help Ensure Equitable Access and Benefitmentioning
confidence: 99%
“…Lack of insurance and economic concerns often are the main barriers for obtaining a genetic risk assessment for hereditary breast and ovarian cancer, and limited English proficiency and cultural factors such as embarrassment, modesty and secrecy also reduce the rate of genetic testing ( 21 ). H/L are willing to engage and have a strong desire for counseling and screening despite barriers they experience ( 21 25 ), however, within a study of 1622 participants recruited through a state cancer registry and who reported receiving genetic testing, H/L were nearly two times less likely as NHW women to report discussing genetic testing with a health provider ( 26 , 27 ). A study on H/L found positive attitudes towards genetic testing for cancer prevention, with 87% agreeing it was a good idea and 87.7% agreeing that everyone should get genetic testing for cancer prevention ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Eligible participants were: (1) female BC survivors; (2) self‐identify as Latina/Hispanic; (3) age ≥25; (4) Spanish‐preferring; (5) GC/GT‐naïve (have not currently scheduled or previously attended GC/GT), and (6) eligible for GC/GT based on National Comprehensive Cancer Network guidelines 15 . Participants were recruited between January and June 2017 through clinic‐ and community‐based approaches 11,14 . Interested individuals called the study and a bilingual research assistant screened them for eligibility.…”
Section: Methodsmentioning
confidence: 99%
“… 14 All the participants in the intervention group and recruited in PR had access to no‐cost GC/GT during the study or after the study. 14 Moffitt Cancer Center (IRB #18601) and Ponce Health Sciences University‐Ponce Research Institute (IRB #160607‐EC) Institutional Review Boards approved study procedures. This study was conducted according to the guidelines of the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%